2022
DOI: 10.1128/spectrum.01834-21
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Communities in the Rhizosphere at Different Growth Stages of Maize Cultivated in Soil Under Conventional and Conservation Agricultural Practices

Abstract: We studied the effect of sustainable conservation agricultural practices versus intensive conventional ones on the soil microbial diversity, potential functionality, and community assembly in rhizosphere of maize cultivated in a semiarid environment. We found that conservation agriculture practices increased the diversity of soil microbial species and functions and strongly affected how they were structured compared to conventional practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 69 publications
0
10
0
2
Order By: Relevance
“…Other work done on willows showed that early microbial community composition could predict the potential of the trees to decontaminate soil or to survive (Bell et al 2014;Yergeau et al 2015). Navarro-Noya et al (2022) showed that the complexity of microbial structure and diversity increases with maize development, and that the effect of agricultural practices on the soil microbiome was more evident at the early stages, which could explain why early microbial indicators performed better. This is encouraging for future work, as the ultimate goal of this type of predictive modeling is to have a tool that could be used to guide management strategies for farmers.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Other work done on willows showed that early microbial community composition could predict the potential of the trees to decontaminate soil or to survive (Bell et al 2014;Yergeau et al 2015). Navarro-Noya et al (2022) showed that the complexity of microbial structure and diversity increases with maize development, and that the effect of agricultural practices on the soil microbiome was more evident at the early stages, which could explain why early microbial indicators performed better. This is encouraging for future work, as the ultimate goal of this type of predictive modeling is to have a tool that could be used to guide management strategies for farmers.…”
Section: Discussionmentioning
confidence: 96%
“…2015). Navarro-Noya et al . (2022) showed that the complexity of microbial structure and diversity increases with maize development, and that the effect of agricultural practices on the soil microbiome was more evident at the early stages, which could explain why early microbial indicators performed better.…”
Section: Discussionmentioning
confidence: 99%
“…Results for SOM parameters (Table 2) such as TOC and TN were not significantly influenced in the three years of CONS management, consistent with the data reported by Muscolo et al [47] while Rakesh et al [48] in a 4-year-long experiment found a significant TOC improvement compared to conventionally managed soils. Microbial biomass and soil enzymatic activities were found to be more reliable factors to depict the soil evolution both in short periods [23,49] and long periods [50]. The significant increase in β-glucosidase activity in CONS indicated an improvement in carbon cycle and the significant differences between the managements suggest an important role of cover crops in the soil evolution under conservative management.…”
Section: Discussionmentioning
confidence: 97%
“…Tabela 1 -Quantidade de artigos publicados sobre o estudo da microbiota de solos agrícolas e as culturas implantadas durante a pesquisa. As plantas influenciam os microrganismos do solo, principalmente na rizosfera, fina camada de solo diretamente impactada pelas raízes das plantas que podem secretar entre 20 a 40% de seus fotossintatos na rizosfera (Navarro-Noya et. al., 2022), estimulando a atividade microbiana (Costa et.…”
Section: Comunidade Microbiana Em Solos Agrícolasunclassified
“…Em um agroecossistema as práticas agrícolas e a cultura cultivada definem a comunidade microbiana presente no solo e as interações mutualística entre estes microrganismos do solo na rizosfera são cruciais na produtividade do sistema (Navarro-Noya et. al., 2022).…”
Section: Culturas Avaliadasunclassified